Electron capture and ionization processes in high velocity Cn+, C-Ar and Cn+, C-He collisions. (July 2015) - Labaigt, G; Jorge, A; Illescas, C; Béroff, K; Dubois, A; Pons, B; Chabot, M
Synopsis: Single and double electron capture as well as projectile single and multiple ionization processes occurring in 125keV/u Cn + -He, Ar collisions have been studied experimentally and theoretically for 1 ≤ n ≤ 5. The Independent atom and electron (IAE) model has been used to describe the cluster-atom collision. The ion/atom-atom probabilities required for the IAE simulations have been determined by classical trajectory Monte Carlo (CTMC) and semiclassical atomic orbital close coupling (SCAOCC) calculations for the Ar and He targets respectively. In general the agreement between experiment and IAE simulations was good, with the exception of double electron capture leading to anionic C − n species.